PENERAPAN PEMBELAJARAN MODIFIKASI PENGGUNAKAN AUDIO VISUAL DALAM MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA GEOGRAFI X.MIA.4 SMA NEGERI 11 PEKANBARU - Ermita Dahliana; Khairani Khairani; Syafri Anwar (Universitas Negeri Padang, 2021)
This study aims to investigate the effectiveness of audio–visual media in improving students’ learning motivation and outcomes on Geography subject in Class X MIA 4, SMA N 11 Pekanbaru.This research is a Classroom Action Research (PTK) conducted in 2 cycles. It seeks to illustrate the increase in students’ motivation and learning outcomes in SMA Negeri 11 Pekanbaru. The research procedure in both cycles has 4 stages, namely: planning, implementation, observation and reflection. Each cycle is done three times. Data were taken through observation. They were analyzed by Percentage formula.The results show that learning motivation in three meetings in cycle l were 40.43%, 42.99%, and 53% respectively. In the 2nd cycle, they were 77.90%, 85.43, and 88.15%. Regarding the students’ learning outcome, the results in the cycle l and II were 43.93% and 86.66% respectively.